The Earthly Paradise : Arts and Crafts by William Morris and his circle from Canadian Collections. - Lochnan, Katharine A.; Schoenherr, Douglas E.; Silver, Carole (Ontario Toronto : Art Gallery of Ontario Key Porter Books Limited, 1993)
Published in conjunction with an exhibition held at the Art Gallery of Ontario in 1993
Engels
The earthly paradise. Arts and crafts by William Morris and his circle from Canadian collections.
kunstcatalogus
Keywords: Morris, William